2020
DOI: 10.1037/dev0000877
|View full text |Cite
|
Sign up to set email alerts
|

The mindful adolescent: Developmental changes in nonreactivity to inner experiences and its association with emotional well-being.

Abstract: Little is known about the naturalistic development of mindfulness in adolescence and how it relates to changes in emotional well-being. The current longitudinal study examined the development of one dimension of mindfulness, nonreactivity to difficult inner experience (or in more colloquial terms, being able to notice, but "take a step back" from distressing thoughts), in a racially and socioeconomically diverse sample (N ϭ 1,657) during the transition from middle school to high school. Students participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…Based on these considerations, it seems critical for researchers to explicitly delineate the experience of motivational conflict, as a potential stressor, from the cognitive-affective evaluation of these conflict experiences, in terms of conflict reactivity (cf., Becker et al, 2019; Galla et al, 2020; Galla & Wood, 2015). In the following, we explain why entertaining such a differentiated perspective should also be important for individuals.…”
Section: Experiencing Motivational Conflictmentioning
confidence: 99%
“…Based on these considerations, it seems critical for researchers to explicitly delineate the experience of motivational conflict, as a potential stressor, from the cognitive-affective evaluation of these conflict experiences, in terms of conflict reactivity (cf., Becker et al, 2019; Galla et al, 2020; Galla & Wood, 2015). In the following, we explain why entertaining such a differentiated perspective should also be important for individuals.…”
Section: Experiencing Motivational Conflictmentioning
confidence: 99%
“…Considering the results, it is important to diminish these levels of negative affect in students by means of techniques or strategies that have shown to be beneficial for positive affect and detrimental for negative affect. These strategies would include cognitive restructuring, mindfulness, and the promotion of self-esteem and motivation, among others (Shikatani et al, 2014;Gómez-Baya et al, 2018;Galla et al, 2020). Likewise, it would be advisable to use programs such as INTEMO (Ruiz-Aranda et al, 2013), which aims to develop emotional skills in adolescents and has shown positive results in reducing certain attitudes toward school dysfunction and other variables such as anxiety, stress, or depression.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the mindfulness-based interventions have revealed significant reductions in stress levels. [53][54][55] For the remaining profiles, although it was to be expected that the Low School Refusal Behavior would be the most representative profile (47.7%) because of the type of a community sample, it is important to note that a very high percentage of students (46.6%) belongs to the School Refusal Behavior by Positive Reinforcement. This group is characterized by pursuing tangible reinforcements outside of school.…”
Section: Discussionmentioning
confidence: 99%